Role of Anti-mullerian Hormone (AMH), As A Prediction of Clinical Pregnancy Outcome in Women with Polycystic Ovarian Syndrome with Sub Fertility (Journal of Shaheed Suhrawardy Medical College, 2018)
Background: Anti-mullerian hormone (AMH) in largely expressed throughout folliculogenisis (by granulosa cells in ovarian follicles) but highest in pre-antral and small antral steges (